2020
DOI: 10.21037/jhmhp-20-78
|View full text |Cite
|
Sign up to set email alerts
|

Expanding smoke-free communities: attitudes and beliefs surrounding smoke-free casinos and bars in Washoe County, Nevada

Abstract: Background: In 2006, Nevada voters approved the Nevada Clean Indoor Air Act, which prohibited smoking in many public places but exemptions still allowed smoking in casinos and 21-and-over bars. The 2016 Nevada Adult Tobacco Survey showed support for prohibiting smoking in casinos (52.9%) and bars (44.6%) but a more detailed understanding of the current level of support-or lack thereof-for 100% smoke-free locations in Washoe County is needed.Methods: A web-based survey was administered to Washoe county resident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…And not the government telling us, you shouldn’t do this, because again with the slippery slope. Where does it end?” ( Crosbie et al, 2020 )…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…And not the government telling us, you shouldn’t do this, because again with the slippery slope. Where does it end?” ( Crosbie et al, 2020 )…”
Section: Resultsmentioning
confidence: 99%
“…Where does it end?" (Crosbie et al, 2020) Sociocultural environment -group formation Cultural identity (n = 34). Across smoking and COVID-19 literature, differences were observed in societal norms across cultures and religions regarding preventive health behaviours.…”
Section: Political Environment -Facilitates Change and Shifts Perspec...mentioning
confidence: 99%
“…Given the gaps in protection offered by the 2006 NCIAA, it is important for policymakers in Nevada to amend the NCIAA and prohibit smoking in all public places including casinos and bars in Nevada. Policymakers in Nevada have stated they would strengthen the NCIAA if their constituents supported such a move [ 31 ] and a recent survey of local Reno and Sparks citizens found that 74 % of non-smokers indicated they would favor a law prohibiting smoking in all casinos [ 19 ]. If policymakers are unable to amend the NCIAA and support for smoke-free casinos continues to increase, health advocates could also help create and support a statewide ballot measure to bring this decision to Nevada voters.…”
Section: Discussionmentioning
confidence: 99%
“…Given that most casinos in Nevada advertise their properties as family friendly establishments, the NCIAA is increasingly seen as out of date. Families choose to frequent the restaurants, arcades, spas, bowling allies, among other family activities [ 19 ]. We are not aware of studies that have focused on the exposure to minors in casinos or the application of low-cost real-time mobile sensors, and accompanying mobile apps, which have the potential to support widespread community deployment and data-driven community activity.…”
Section: Introductionmentioning
confidence: 99%